qnrVC occurs in different genetic contexts in Klebsiella and Enterobacter strains isolated from Brazilian coastal waters - Gabriela B. Kraychete; Larissa A.B. Botelho; Pedro V. Monteiro-Dias; Wydemberg J. de Araújo; Celso J.B. Oliveira; Ana Paula D. Carvalho-Assef; Rodolpho M. Albano; Renata C. Picão; Raquel R. Bonelli (Journal of Global Antimicrobial Resistance, 2022)
ABSTRACT: Objectives: In contrast to other qnr families, qnrVC has been reported mainly in Vibrio spp. and inserted in class 1 integrons. This study aimed to identify the variants of qnrVC genes detected in Klebsiella pneumoniae carbapenemase-2-producing Enterobacter and Klebsiella strains isolated from Brazilian coastal waters and the genetic contexts associated with their occurrence. Methods: qnrVC variants were identified by Sanger sequencing. Stains were typified by pulsed-field gel electrophoresis. Antimicrobial susceptibility testing, conjugation assays, and whole genome sequencing (WGS) were applied to identify the strains’ antimicrobial resistance profile, qnrVC and blaKPC-2 co-transference, and qnrVC genetic context. Results: qnrVC1 was identified in 15 Enterobacter and 3 Klebsiella, and qnrVC4 in 2 Enterobacter strains. Pulsed-field gel electrophoresis revealed 12 clonal profiles of Enterobacter and one of Klebsiella. Strains were resistant to aminoglycosides, beta-lactams, fosfomycin, quinolones, and sulfamethoxazole-trimethoprim. Co-transference of qnrVC and blaKPC-2 were obtained from five representative Enterobacter strains, which showed resistance to ampicillin and amoxicillin-clavulanate, and reduced susceptibility to extended-spectrum cephalosporins, meropenem, and ciprofloxacin. WGS analysis from representative strains revealed one K. quasipneumoniae subsp. similipneumoniae, one E. soli, four E. kobei, and seven isolates belonging to Enterobacter Taxon 3. Long-read WGS showed qnrVC and blaKPC-2 were carried by the same replicon on Klebsiella and Enterobacter strains, and the qnrVC association with not previously described genetic environments composed of insertion sequences and truncated genes. These contexts occurred in small- and high-molecular-weight plasmids belonging to IncFII, IncP6, pKPC-CAV1321, and IncU groups. Conclusion: Our results suggest that the dissemination of qnrVC among Enterobacterales in Brazilian coastal waters is associated with several genetic recombination events.